Predictive validity of the adult tobacco dependence index: Findings from waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) study - Strong, David R. (Drug Alcohol Depend, 2020)
BACKGROUND AND AIMS: Building on published work() establishing concurrent validity of a self-report tobacco dependence (TD) index among users of different tobacco products in Wave 1 (W1) of the Population Assessment of Tobacco and Health (PATH) Study, the current study examines prospective relationships with tobacco use behaviors to establish predictive validity of the TD index. Hypotheses suggested high levels of W1 TD would be associated with persistent tobacco use at Wave 2 (W2). PARTICIPANTS: A U.S. nationally representative sample of 32,320 adult W1 and W2 interviews focused on 11,615 W1 adults who were current established tobacco users and completed the W2 interview. FINDINGS: Higher TD scores and greater changes in TD scores were associated with greater quantity and frequency of tobacco use at the W2 interview for Cigarette Only (n=7068), Smokeless (smokeless or snus pouches) Only (n=772), Cigarette plus E-Cigarette (n=592), and Multiple Products (n=1866) users, although not significantly so for E-Cigarette Only (n=367), Cigar Only (traditional, cigarillo, or filtered) (n=584), or Hookah Only (n=366) users. Higher TD was associated with decreased odds of successful quitting for Cigarette and Multiple Product users. Higher TD was associated with increased odds of a quit attempt for those in the Hookah and Multiple Products user groups and was not associated with quit attempts or deceased odds of quit success among exclusive E-Cigarette, Cigar, Smokeless and Cigarette plus E-Cigarette users. CONCLUSION: Support for the predictive validity of the PATH Study measures of adult TD will enable regulatory investigations of TD across several tobacco products.